Economic Order Quantity (EOQ) Analysis In Efforts To Improve Efficiency In Hawayu Coffee & Eatery Bandung - Fajri, Ilham; Maima, Amsal (Universitas Pendidikan Indonesia, 2020)
Economic Order Quality (EOQ) is the stockpile economic method which is used in order to decide the company amount of order. This research is aimed to find the comparison of conventional method and Economic Order Quality (EOQ) related to the company’s cost efficiency in Hawayu Coffee Eatery.Experimental design was chosen as a method in this research. The primary and secondary data were used as data analysis. The need and the cost of raw material of the company in range of October 2019 until January 2020 were taken as the secondary data while the frequency of order, order cost and saving cost were taken as the primary data. The Economic Order Quantity (EOQ) and the cost efficiency of total stockpile were used also as the tools of the analysis. The result shows that the Economic Order Quantity (EOQ) method has given a significant result on the efficiency cost of the total raw material stockpile in 90,8% for groceries and 78,7 % for perishable. In sum, if the Economic Order Quantity (EOQ) is fully thoroughgoing record, the Economic Order Quantity (EOQ) could be applied in a correct way. The Economic Order Quantity (EOQ) is effectively applied in order to increase the cost efficiency in Hawayu Coffee Eatery.